Pengaruh Posisi Tripod Terhadap Saturasi Oksigen Pada Pasien PPOK - Putri, Zahra Adiya; Fadhani, Masyithah (JKM : Jurnal Keperawatan Merdeka, 2025)
Background: One common manifestation found in COPD patients is decreased oxygen saturation (hypoxemia), especially during episodes of shortness of breath (dyspnea). This condition not only worsens the patient's quality of life but also increases the risk of complications and mortality. In clinical practice, COPD patients often instinctively adopt a forward-leaning sitting posture with hands resting on the knees or a table, known as the tripod position. This position is believed to enhance ventilation efficiency by assisting accessory respiratory muscles such as the pectoralis major and minor to work more optimally, expanding the thoracic cavity, and reducing the workload on the diaphragm. This study aims to determine the effect of the tripod position on oxygen saturation in COPD patients Methods: This research used a pre-experimental, pretest-posttest one-group design. The sample consisted of 14 respondents selected through purposive sampling Data were collected using an observation sheet and standard operating procedures, measuring oxygen saturation with a pulse oximeter before and after the tripod position intervention. Results: Data analysis was conducted using the Paired Sample t-Test. The univariate results showed the mean oxygen saturation before the intervention (pretest) was 89.86%, and after the intervention (posttest), it increased to 92.93%. The bivariate statistical test showed a p-value of 0.001, where p < 0.05. Conclusion: It can be concluded that the tripod position significantly affects oxygen saturation in COPD patients on the 2nd floor of RSU Madina Bukittinggi in 2025. The tripod position has been proven to significantly increase oxygen saturation in COPD patients and is recommended as a simple, cost-effective, and non-pharmacological intervention for managing dyspnea. It can also be used as part of patient education by healthcare professionals.